Halyna Hubareva: CONTRAPOSITION OF THE INTIMATE LYRIC POETRY OF IRYNA FOTUIMA - Kalashnyk, Yuliia (Linguistic Bulletin (Movoznavchyi Visnyk), 2022)
Аbstract. Introduction. The study of Iryna Fotuima’s writing style makes it possible to trace the demonstrative means and methods of expression of the contrast as a manifestation of the individual style. The variety of oppositions forms a special poetic picture of the world, which figuratively conveys the palette of feelings, their polarity. Purpose. The purpose of the research is to examine the lexical-semantic expression, syntactic design and functional load of contradictions in the language of Iryna Fotuima’s poetry included in the collection “Tryvki rubezhi” (2021), having defined the author’s specific guidelines. Results. Among the stylistic methods of verbalization of opposing relations, the antithesis prevails. In I. Fotuima’s poetic texts this figure is formed within a simple sentence by closed homogeneous lines with the semantics of mutual exclusion, the sequence of phenomena. The opposition of attributive and predicate syntaxemes concerns the modification of the same verbal image. In the studied lyrical texts, different types of antithetical relations are realized mostly within complex sentences and supra-phrase units. Even if the basis of contrast is formed by common antonyms, the poetess semantically complicates the created image (by syntagmatic opening, the introduction of comparative constructions). Verbal images based on two-, three-part antithesis are used, in which case we may observe the antithetical parallelism, which creates the density and fury of the poetic image. The antithesis in I. Fotuima’s poetry functions in various predicative parts of a complex sentence that forms a stanza. Quite often the antithesis placed in the first predicative part serves to unfold the verbal image; can be formed at the end of a complex sentence as a kind of generalization. Sometimes contraposition becomes a kind of framing. For some poetry, different types of contrasts are the leading compositional technique. Implicit contrasts, paradoxical meanings often generate contraposition. Originality. In the lyrical texts of the poetess, one-syllable antitheses are realized mainly within homogeneous parts of the sentence, sometimes by object extenders to homogeneous predicates, as well as predicate and attributive syntaxemes. The poetess semantically complicates the contrasting images with common antonyms. I. Fotuima tends to create original antitheses, the centre of which is a multi-part contextual antonymy. In the studied texts, detailed metaphorical images based on contrasts are embodied mainly in complex syntactic constructions, as well as within supra-phrase units. The antithesis is enhanced by gradations, repetitions, parallelism, chiasm. Oxymoron images acquire a special expression. Sometimes implicit contraposition has paradoxical semantics. Quite often the semantics of contrast are expressed by author’s individual comparisons. Antithetical images, depending on the position in the stanza, serve to unfold or generalize poetic semantics. At the same time, for some poetry the contraposition becomes the leading text-making technique. Conclusion. Iryna Fotuima’s intimate lyric poetry testify to the richness of linguistic images built on opposition, which is an indicative feature of her individual style. The author’s antitheses are mostly polynomial, the antithetical relations are realized by the original contextual antonymy. The detailed metaphorical images created on contrasts are embodied mainly in complex syntactic constructions. At the heart of several poems in the collection is a thorough contraposition. Modern poetry provides rich material for tracing the patterns of expressive syntax.